Prognostic value of umbilical and cerebral Doppler in fetal growth restriction: comparison of dichorionic twins and singletons. - Sarah Vanlieferinghen; Olivia Anselem; Camille Le Ray; Yao Shen; Louis Marcellin; François Goffinet (PLoS ONE, 2015)
OBJECTIVE:To compare the prognostic value of fetal Doppler in dichorionic twins and singletons by measuring the interval between diagnosis of an abnormal Doppler flow and birth in fetuses who are small for gestational age (SGA). DESIGN:Comparative retrospective study using a prospectively collected database. SETTING:A level 3 maternity unit in France. POPULATION:Fetuses from singleton and dichorionic pregnancies who are SGA (vascular or unexplained), defined by an abdominal circumference (AC) measurement below the 10th percentile and confirmed by a birth weight below the 10th percentile. METHODS:Fisher's exact and Chi-2 tests were used to compare frequencies, and the Mann-Whitney-Wilcoxon test was used to compare medians in non-Gaussian distributions. MAIN OUTCOME MEASURES:Both neonatal outcomes and intervals between the first Doppler abnormality and birth were compared in the groups of dichorionic twins and singletons. RESULTS:Obstetric and neonatal outcome were similar in the 104 SGA dichorionic twins and 170 SGA singletons. Abnormalities of umbilical artery Doppler, regardless of type, appeared at the same frequency in both groups (52.9%) but were identified earlier in twins (25 versus 28 weeks, p = 0.02). Among fetuses with abnormal Doppler flow, the interval between the finding and birth was significantly longer in the twins than the singletons (44 vs 15 days, p<0.01). CONCLUSIONS:The prognostic value of an abnormal Doppler finding for the course of a pregnancy may be different in dichorionic twins and singletons. The management of women carrying SGA twins and the information provided to them should take these results into account.